The Influence of Lifestyle, Content Marketing, and Brand Trust on Purchase Decisions for Glad2Glow Moisturizer - Zulkarnain, Eka Zuliana; Sardanto, Rino (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This study aims to determine how lifestyle, marketing content and brand trust influence the decision to purchase Glad2Glow moisturizer. Design/Methode/Approach : Using a quantitative approach with causality techniques. The population in this study were UNP Kediri Faculty of Economics and Business Students Class of 2021 who had purchased and used the Glad2Glow moisturizer product at least once. The sample used was 50 respondents who were taken using a non-probability technique with purposive sampling. The technique used in data collection was using a questionnaire and answered based on a Likert scale. The data analysis technique used a multiple linear regression analysis model with statistical analysis including validity and reliability tests, classical assumption tests, multiple linear regression tests, coefficient of determination tests and hypothesis tests, using SPSS for Windows version 27 software. Research Finding : The results of this study partially show that lifestyle variables have a significant effect on purchasing decisions. Marketing content variables do not have a significant effect on purchasing decisions. Brand trust variables have a significant effect on purchasing decisions. However, simultaneously, lifestyle variables, marketing content, and brand trust have a significant effect on purchasing decisions. Theoretical contribution/Originality : This study can provide theoretical contributions by expanding understanding of the influence of lifestyle, marketing content, and brand trust on purchasing decisions for Glad2Glow moisturizer. Practitionel/Policy implication : This research is expected to add to the academic literature review. And Glad2Glow managers can integrate these three aspects to improve product competitiveness. Research limitation : This study only focuses on lifestyle variables, marketing content, and brand trust on purchasing decisions.